Dosimetric characteristics of fabricated silica fibre for postal radiotherapy dose audits - Ahmad Fadzil, Muhammad Safwan; Ramli, N. N. H.; Jusoh, M. A.; Kadni, Taiman; Bradley, David A.; Ung, Ngie Min; Hashim, Suhairul; Mohd Noor, Noramaliza (IOP Publishing, 2014)
Present investigation aims to establish the dosimetric characteristics of a novel fabricated flat fibre TLD system for postal radiotherapy dose audits. Various thermoluminescence (TL) properties have been investigated for five sizes of 6 mol% Ge-doped optical fibres. Key dosimetric characteristics including reproducibility, linearity, fading and energy dependence have been established. Irradiations were carried out using a linear accelerator (linac) and a Cobalt-60 machine. For doses from 0.5 Gy up to 10 Gy, Ge-doped flat fibres exhibit linearity between TL yield and dose, reproducible to better than 8% standard deviation (SD) following repeat measurements (n = 3). For photons generated at potentials from 1.25 MeV to 10 MV an energy-dependent response is noted, with a coefficient of variation (CV) of less than 40% over the range of energies investigated. For 6.0 mm length flat fibres 100 μm thick × 350 pm wide, the TL fading loss following 30 days of storage at room temperature was < 8%. The Ge-doped flat fibre system represents a viable basis for use in postal radiotherapy dose audits, corrections being made for the various factors influencing the TL yield.